What families in the UK use to manage attention-deficit/hyperactivity disorder (ADHD): a survey of resource use. Issue 1 (25th November 2020) - Fibert, Philippa; Relton, Clare
Abstract : Objective: To identify interventions being used to manage attention-deficit/hyperactivity disorder (ADHD) in the UK. Design: A survey within the Sheffield Treatments for ADHD Research project. A convenience sample of participants in the UK who consented to join an observational cohort were asked closed questions about medication, behavioural change programmes and service use, and an open-ended question about what else they used. Setting: A broad variety of non-National Health Service, non-treatment seeking settings throughout the UK, including local authority organisations, schools, ADHD and autism spectrum condition support groups and social media. Participants: Families of children aged 5–18 with carer reported ADHD and Conners Global Index (CGI) T scores of 55+. Results: Responses from 175 families were analysed. The mean age of the children was 10.21 (2.44), and two-thirds (n=114) had additional diagnoses. The majority used medications to manage ADHD (n=120) and had participated in a parenting class (n=130). Just over a quarter (28%, n=49) did not use ADHD medications, and used sleep medications. Just under half had consulted psychologists (n=83), and 32 had participated in other talking therapies such as psychotherapy, counselling and cognitive–behavioural therapy. A few used aids such as reward charts or fiddle toys (n=17) and participated in activities (mostly physical) (n=14). A substantial minority (78/175) had used non-mainstream treatments, the most popular being homoeopathy (n=32), nutritional interventions (n=21) and bodywork such as massage or cranial osteopathy (n=9). Conclusions: Families reported use of a wide variety of treatments to help with management of their children with ADHD in addition to their use of mainstream treatments.